2018
DOI: 10.1016/j.ehj.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Can enhanced external counter pulsation as a non-invasive modality be useful in patients with ischemic cardiomyopathy after coronary artery bypass grafting?

Abstract: BackgroundAngina symptom in patients with ischemic cardiomyopathy (ICM) after coronary artery bypass grafting (CABG) surgery is a major challenging problem in practice. The choice among different treatment modalities available can be judged by different parameters especially measuring the risk/cost ratio to achieve the benefit. Enhanced external counter pulsation (EECP) is one of safest noninvasive modality for treatment of angina as well as it has an anti-failure effect.Patients and method42 patients with ICM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…EECP was shown to be effective in treating angina in patients with ischemic cardiomyopathy after CABG [11] although this is a small study with only 40 subjects. More studies are needed in this group of patients before it can be formally recommended.…”
Section: Resultsmentioning
confidence: 89%
“…EECP was shown to be effective in treating angina in patients with ischemic cardiomyopathy after CABG [11] although this is a small study with only 40 subjects. More studies are needed in this group of patients before it can be formally recommended.…”
Section: Resultsmentioning
confidence: 89%
“…Importantly, in the qualitative results, we also found that patients with angina were more likely to have negative attitude, they had a wrong understanding that angina pectoris is an incurable disease, such practical issues need to be considered. In fact, they did not know that 35 h course of EECP has been shown to relieve angina attacks and reduce the use of nitroglycerin, which may also be related to a lack of physician advice and encouragement (34,35). The intensity of physician encouragement was reported to be a key factor in determining patients to participate and adhere to cardiac rehabilitation (36).…”
Section: Discussionmentioning
confidence: 99%